Rates of depression, anxiety, and stress in parents of children with congenital heart disease using the Depression Anxiety Stress Scale - Brian K Lee; Rohit S Loomba (Wolters Kluwer Medknow Publications, 2022)
Context and Background : The Cardiac Neurodevelopmental Outcome Collaborative has recommended using the Depression Anxiety Stress Scale (DASS) to evaluate for depression, anxiety, and stress in parents of children with congenital heart disease (CHD). There has not been a longitudinal study investigating its utility in these parents. Aims : The aim of this study was to determine the trend of depression, anxiety, and stress in parents of patients with CHD. Methods : Our center uses this self-reported survey at every visit between 6 and 36 months of age. This was a single-centered, retrospective study from January 1, 2018, to June 1, 2020. Statistical Analysis : Cox regression analysis was conducted using a composite end point of having an abnormal score in any of the three domains. Results : Two hundred and seventy-three mothers and 139 fathers were included in the study. For mothers, scores in each domain were elevated at 12 and 24 months. For fathers, scores in each domain were elevated at 6 months, followed by a decrease before peaking again, with depression increasing at 36 months and anxiety and stress increasing at 30 months. Increased length of stay for the index surgery was associated with an abnormal score for mothers (B = 0.02, P < 0.01) and fathers (B = 0.01, P = 0.04). Being in a relationship with the father (B = -0.8, P < 0.01) was associated with freedom of an abnormal score for mothers. Conclusions : Scores concerning for depression, anxiety, and stress peak at different points for parents. Length of stay for the index surgery and being in a relationship are important factors in the mental health of parents.